Free Radical Scavenging Potential of Jatropha gossypifolia - Kharat, A.R.; Dolui, A.K.; Das, S. (Asian Journal of Chemistry, 2010)
The leaves of Jatropha gossypifolia Linn. known as Bellayche bush is an important Indian medicinal plant. Preliminary phytochemical screening of the plant showed the presence of high amount of phenolics, tannins and flavonoids. Subsequent quantification showed the presence of 8.6 % w/w total phenolics and 7.4 % w/w of flavonoids. This high amount of phenolics and flavonoids prompted us to evaluate its antioxidant activity. We studied the antioxidant activity of J. gossypifolia in three in vitro models: DPPH free radical, ferric thiocyanate and nitric oxide scavenging method. The methanol, ethyl acetate and aqueous extracts of Jatropha gossypifolia leaves showed significant antioxidant activity. Free radical scavenging activity might be due to the presence of flavonoids.